Exploring unseen worlds: William James and the philosophy of mysticism - Barnard, G. William (State University of New York Press, 1997)
Establishing foundations: ladders and laughing gas, phantoms and fathers -- Experiencing unseen worlds: towards a Jamesian epistemology of mysticism -- "Fields within fields within fields": mysticism and a Jamesian psychology of the self -- Beyond words, beyond morals: the metaphysical and ethical implications of mysticism -- Telling truths, touching realities: spiritual judgments, saints, and pragmatism.